Law Enforcement of Cracking Criminal Actions from The Perspective of Special Criminal Law in Indonesia - Salsabilla, Anggi Afrita; Hariyana, Trinas Dewi; Manfaluthi, Agus (Faculty of Law, Kadiri Islamic University (UNISKA) Kediri, 2024)
The development of information technology has not only positive but also negative impacts in the form of the emergence of cracking crimes. Although in Indonesia there are provisions that accommodate cracking, there are still obstacles in enforcing the law. This study aims to analyze the legal regulations for cracking crimes and the effectiveness of legal protection regulations for victims of cracking crimes from the perspective of special criminal law in Indonesia. The type of research used is normative legal research. The results of this study indicate that first, related to cracking crimes in Indonesia, it has been accommodated through Article 30 paragraph (3) and Article 46 paragraph (3) of the ITE Law 19/2016. Meanwhile, the PDP Law does not explicitly accommodate cracking crimes. However, Article 65 paragraph (1) and Article 67 paragraph (1) of the PDP Law imply elements of cracking acts in the form of illegal access to personal data. The effectiveness of the ITE Law 19/2016 and the PDP Law is still not sufficient in combating cracking crimes and providing legal protection for victims. This is a challenge for the police. The challenges are classified into four aspects of obstacles, namely: the investigation aspect, the evidence aspect, the facilities aspect, and the jurisdiction aspect. Efforts to overcome these obstacles are: (1) Special training is needed to provide investigators with an understanding of the cyber world; (2) Expert skills are needed with the help of the latest technology to analyze evidence that is at risk of being easily modified, deleted, or hidden by the perpetrator; (3) Facilities are needed that can support police performance through optimizing digital forensic skills; and (4) More attention is needed to mapping places/physical areas related to the occurrence of cybercrime.